P‐53: Research on Full‐Screen Notch of LTPS LCD. Issue 1 (30th May 2018) - Xie, Huimin; Li, Donghua; Wang, Zhijie; Zhou, Xiufeng; Shen, Boping; Li, Junyi
Abstract : In recent years, the full screen mobile phone has developed rapidly. Because the full screen not only improves the value of the mobile phone, but also makes the mobile phone more scientific and technological. Moreover, it can accommodate larger screens for the same size phone body, and has a significant improvement in visual experience. This research adopts reasonable circuit to realize a 0.75mm narrow frame full screen. Its notch width is 21.22mm and the depth is 5.23mm. By optimizing the circuit, the difference between the main screen and the secondary screen is reduced. It allows users to get the best impression.